Soluble Epoxide Hydrolase Inhibition Prevents Experimental Type 4 Cardiorenal Syndrome - Hamzaoui, Mouad; Roche, Clothilde; Coquerel, David; Duflot, Thomas; Brunel, Valery; Mulder, Paul; Richard, Vincent; Bellien, Jérémy; Guerrot, Dominique (Frontiers in Molecular Biosciences, 2021)
Objectives: Cardiovascular diseases (CVD) remain the leading cause of morbimortality in patients with chronic kidney disease (CKD). The aim of this study was to assess the cardiovascular impact of the pharmacological inhibition of soluble epoxide hydrolase (sEH), which metabolizes the endothelium-derived vasodilatory and anti-inflammatory epoxyeicosatrienoic acids (EETs) to dihydroxyeicosatrienoic acid (DHETs), in the 5/6 nephrectomy (Nx) mouse model. Methods and Results: Compared to sham-operated mice, there was decrease in EET-to-DHET ratio 3 months after surgery in vehicle-treated Nx mice but not in mice treated with the sEH inhibitor t-AUCB. Nx induced an increase in plasma creatinine and in urine albumin-to-creatinine ratio as well as the development of kidney histological lesions, all of which were not modified by t-AUCB. In addition, t-AUCB did not oppose Nx-induced blood pressure increase. However, t-AUCB prevented the development of cardiac hypertrophy and fibrosis induced by Nx, as well as normalized the echocardiographic indices of diastolic and systolic function. Moreover, the reduction in endothelium-dependent flow-mediated dilatation of isolated mesenteric arteries induced by Nx was blunted by t-AUCB without change in endothelium-independent dilatation to sodium nitroprusside. Conclusion: Inhibition of sEH reduces the cardiac remodelling, and the diastolic and systolic dysfunctions associated with CKD. These beneficial effects may be mediated by the prevention of endothelial dysfunction, independent from kidney preservation and antihypertensor effect. Thus, inhibition of sEH holds a therapeutic potential in preventing type 4 cardiorenal syndrome.